2007
DOI: 10.1002/rcs.161
|View full text |Cite
|
Sign up to set email alerts
|

Results of total hip replacement using the Robodoc surgical assistant system: clinical outcome and evaluation of complications for 97 procedures

Abstract: Robotic-assisted total hip arthroplasty with the Orthodoc/ Robodoc system achieves equal results as compared to a manual technique. However, there was a high number of technical complications directly or indirectly related to the robot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(81 citation statements)
references
References 32 publications
1
76
1
3
Order By: Relevance
“…Schulz et al reported heterotopic ossifications after robotic-milling THA were found in 27.8% of patients, although they had no control group [22]. In our series, heterotopic ossification was seen in 20 hips (26.6%) in the robotic-milling group.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Schulz et al reported heterotopic ossifications after robotic-milling THA were found in 27.8% of patients, although they had no control group [22]. In our series, heterotopic ossification was seen in 20 hips (26.6%) in the robotic-milling group.…”
Section: Discussioncontrasting
confidence: 43%
“…There have been several reported complications with this system including soft tissue problems, gait abnormalities, and femoral fissures that have limited its use in Europe [22]. In 2003, Honl et al reported a higher dislocation rate of 18% and subsequent revision rate of 15% in a robotic-assisted group [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Subsequent applications in hip replacement and knee arthroplasty have demonstrated improved results with newer designs. 10,16,19 Applying the da Vinci robotic system, widely used in general surgery and urology, 8 has revealed that the device has limited application…”
Section: Discussionmentioning
confidence: 99%
“…As a result, robots have been increasingly included to assist the surgeon, including the orthopedic robot RoboDoc (Curexo Technology, Fremont, CA, USA) [10], the robotic system ZEUS [11], and the robotic Da Vinci system [12] used for minimally invasive surgery, the endovascular micro [13], and the intestinal capsule robot [14,15]. With the development of three-dimensional imaging, navigation, and medical robotics, robotic assistance for mandibular reconstructive surgery has been introduced.…”
Section: Introductionmentioning
confidence: 99%